Türkiye Florası İçin Yeni Bir Tür Kaydı: Astragalus schmalhausenii Bunge (Fabaceae) - Karaman, Seher; Duman, Hayri; Evren, Ahmet Harun; Aytaç, Zeki (İstanbul Üniversitesi, 2023)
Bu çalışmada, Doğu Anadolu Bölgesi Elazığ ilinden toplanan Astragalus schmalhausenii Bunge’nin Türkiye Florası için yeni bir kayıt olduğu belirlenmiştir. Kazakistan, Türkmenistan, Özbekistan, Kırgızistan, Afganistan ve İran’da doğal olarak yayılış gösterir. Türün betimi ve olarak ayırt edici özellikleri, fotoğrafı ve yayılış haritası verilmiştir. Bu kayıt ile birlikte Astragalus L. cinsi Oxyglottis Bunge seksiyonuna ait tür sayısı 2’ye çıkmıştır.

In this study, it has been determined that Astragalus schmalhausenii Bunge, collected from the Eastern Anatolia Region, specifically in the Elazığ province, is a new record for the Flora of Turkey. This species is naturally distributed in Kazakhstan, Turkmenistan, Uzbekistan, Kyrgyzstan, Afghanistan, and Iran. A detailed description of the species, diagnostic characters, photograph, and a distribution map are provided. With this record, the number of species belonging to the section Oxyglottis Bunge of the genus Astragalus L. has increased to 2.
A New Record for the Flora of Turkey: Astragalus schmalhausenii Bunge (Fabaceae)
Keywords: Botany (Other); Bitki Bilimi (Diğer)